Low-pH induced reversible reorganizations of chloroplast thylakoid membranes - As revealed by small-angle neutron scattering - Ünnep, Renáta; Zsiros, Ottó; Hörcsik, Zsolt; Markó, Márton; Jajoo, Anjana; Kohlbrecher, Joachim; Garab, Győző; Nagy, Gergely (Biochimica et biophysica acta. Bioenergetics, 2017)
Energization of thylakoid membranes brings about the acidification of the lumenal aqueous phase, which activates important regulatory mechanisms. Earlier Jajoo and coworkers (2014 FEBS Lett. 588:970) have shown that low pH in isolated plant thylakoid membranes induces changes in the excitation energy distribution between the two photosystems. In order to elucidate the structural background of these changes, we used small-angle neutron scattering on thylakoid membranes exposed to low p2H (pD) and show that gradually lowering the p2H from 8.0 to 5.0 causes small but well discernible reversible diminishment of the periodic order and the lamellar repeat distance and an increased mosaicity - similar to the effects elicited by light-induced acidification of the lumen. Our data strongly suggest that thylakoids dynamically respond to the membrane energization and actively participate in different regulatory mechanisms.
Keywords: listy rostlin; fluidita membrány; Chloroplast thylakoid membranes; koncentrace vodíkových iontů; Thylakoids; Plant Leaves; hrách setý; Lamellar repeat distance; Photosystem II Protein Complex; Hydrogen-Ion Concentration; neutronová difrakce; maloúhlový rozptyl; fotosyntéza; Membrane Fluidity; Neutron Diffraction; Photosystem I Protein Complex; tylakoidy; Pisum sativum; Photosynthesis; Small-angle neutron scattering (SANS); Energy Transfer; fotosystém II (proteinový komplex); Low pH and p(2)H; fotosystém I (proteinový komplex); Scattering, Small Angle; přenos energie